Georgic modernity and British romanticism : - Goodman, Kevis (Cambridge University Press, 2004)
Kevis Goodman, an Associate Professor of English Literature at the University of California, Berkeley, traces connections between georgic verse and developments in other spheres that were placing unprecedented emphasis on mediation from the late seventeenth to early nineteenth centuries. She expands the subject of the Georgic to broader areas of literary and cultural study--including the history of the feelings, print culture, and early scientific technology.